2014
DOI: 10.1371/journal.pone.0115243
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Role of the Polysaccharide Capsule Transport Proteins in Pertussis Pathogenesis

Abstract: Polysaccharide (PS) capsules are important virulence determinants for many bacterial pathogens. Bordetella pertussis, the agent of whooping cough, produces a surface associated microcapsule but its role in pertussis pathogenesis remained unknown. Here we showed that the B. pertussis capsule locus is expressed in vivo in murine lungs and that absence of the membrane-associated protein KpsT, involved in the transport of the PS polymers across the envelope, but not the surface-exposed PS capsule itself, affects d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…In line with these observations, the expression of virulence repressed gene vrg6 was induced during the infection. Of note, increased expression of vrg6 gene was observed also in B. pertussis cells recovered from lungs of intranasally infected mice [74]. While this gene was one of the first described virulence repressed genes in B. pertussis [75], its cellular function remained unclear.…”
Section: Discussionmentioning
confidence: 98%
“…In line with these observations, the expression of virulence repressed gene vrg6 was induced during the infection. Of note, increased expression of vrg6 gene was observed also in B. pertussis cells recovered from lungs of intranasally infected mice [74]. While this gene was one of the first described virulence repressed genes in B. pertussis [75], its cellular function remained unclear.…”
Section: Discussionmentioning
confidence: 98%
“…Some shared modules are rare in their distribution among prokaryotes, including pathways for polyamine biosynthesis (M00134), vitamin and cofactor biosynthesis (M00124 and M00121), drug efflux (M00720), as well as transport systems for biotin (M00581), capsular polysaccharide (M00249), rhamnose (M00220), and l -arabinose or lactose (M00199). These rare modules have been shown to contribute to stress tolerance, viability, or virulence in some microbes ( 23 25 ). Benzoate degradation (M00551) is a restricted, rare pathway that is also shared by MAGs of the leachate and river metagenomes.…”
Section: Resultsmentioning
confidence: 99%
“…The cellular benefit or function of the Bordetella modulation response is unknown although the Bvg− phase is thought to be important for survival outside of a host or for transmission between hosts (Cotter and Miller, ). However, recent studies indicate that Bordetella cells do experience Bvg− conditions in vivo (Mason et al ., ; Hoo et al ., , Dewan et al ., ). In another study, investigators identified B .…”
Section: Discussionmentioning
confidence: 99%
“…The cellular benefit or function of the Bordetella modulation response is unknown although the Bvg2 phase is thought to be important for survival outside of a host or for transmission between hosts (Cotter and Miller, 1997). However, recent studies indicate that Bordetella cells do experience Bvg2 conditions in vivo (Mason et al, 2013;Hoo et al, 2014, Dewan et al, 2017. In another study, investigators identified B. bronchiseptica brtA, a lapA ortholog, and demonstrated it was a Bvg2 phase gene involved in biofilm formation and expressed in infected rat trachea (Nishikawa et al, 2016).…”
Section: Discussionmentioning
confidence: 99%